ANALYSIS OF THE TORSION PROBLEM ON TRANSVERSALLY ISOTROPIC LIGHT GAUGE CYLINDER WITH VARIABLE SHEAR MODULUS - Sevda B. Akperova (Advanced Engineering Research, 2010)
A torsion problem on the transversally isotropic hollow light gauge cylinder with variable shear modules is studied on the ground of the homogeneous solution method. Asymptotic expansions of homogeneous solutions are obtained, and cylinder stress-strain state is analyzed.